Influence of male parental on germinative power of oil palm seeds - Zambrano Marcillo, Silvia Madelein (2024)
The National Institute of Agricultural Research (INIAP) uses female parentals (Dura - Deli) and male parentals (Pisifera) from different origins to obtain the hybrid INIAP - Tenera of oil palm (Elaeis guineensis Jacq). The objective was to evaluate the influence of the male parental on the germination of African oil palm seeds. Seeds from 20 bunches, resulting from the crossing of 10 Dura plants with pollen from two Pisifera plants, were subjected to the germination process. The process involved eight days of imbibition 1, 80 days of heating, 24 hours of drying, four days of imbibition 2, and six hours of drying. One hundred seeds per treatment and per repetition were evaluated using a completely randomized design, assisted by Tukey's test at 5%. The results showed that seeds from Dura plants D1, D8, and D9 crossed with the male parental P1 achieved a higher percentage of optimal germination and statistical differences compared to seeds from the same Dura plants crossed with Pisifera P2. Of the 10 Dura progenitors studied, seven (D1, D3, D4, D5, D8, D9, D10) crossed with Pisifera P1 achieved an average optimal germination rate above 50%, while only two of the Dura plants (D3 and D5) evaluated and crossed with Pisifera P2 achieved an optimal germination rate equal to or above 50%. This demonstrated that the germination of Tenera seeds (Dura x Pisifera) of African oil palm is highly related to the male parental use.